Development and Validation of a Self-Awareness Intervention based on Monotheistic Innateness: A Mixed Method Experimental Study of Cognitive Emotion Regulation in Female Adolescents - Khamisi, Leila; Ehteshamzadeh, Parvin; Alireza Heidari; Kalantari, Fariba (Social Determinants of Health, 2025)
Background: A robust sense of self facilitates emotional comprehension, stress management, and adaptive lifestyle behaviors. Incorporating spiritual or religious dimensions can enhance self-awareness and resilience. This study developed and validated a faith-based self-awareness intervention grounded in Islamic epistemology, assessing its effects on cognitive emotion regulation among adolescents. Methods: Employing a sequential mixed-methods design, the qualitative phase utilized Attride-Stirling’s thematic analysis framework to examine library resources, identifying constructs for a self-awareness package rooted in Islamic epistemology, with subsequent expert validation by psychologists. The quantitative phase evaluated efficacy in 30 female secondary students (aged 13–16 years) from Shadegan via a pre-test-post-test control group design. Participants were purposively selected and randomly allocated; the experimental group underwent eight 90-minute sessions, whereas controls received no intervention and were wait-listed. Cognitive emotion regulation was measured using the Cognitive Emotion Regulation Questionnaire (CERQ), with data analyzed via repeated-measures ANOVA in SPSS-23. Results: Qualitative analysis yielded a faith-based self-awareness framework rooted in Islamic epistemology, comprising one overarching theme, five organizing themes, and 22 basic themes. Content validity was affirmed (CVI=0.79; CVR=0.75). Quantitatively, the experimental group exhibited significant gains in adaptive emotion-regulation strategies relative to controls (P<0.001, η²=0.45), confirming intervention efficacy. Conclusion: This mixed-methods investigation validates an Islamic epistemology-based self-awareness package, evidencing improved adaptive emotion regulation in adolescents. Results underscore the promise of epistemologically aligned interventions for bolstering psychological well-being and interpersonal functioning.